High strength and flexible aramid nanofiber conductive hydrogels for wearable strain sensors. Issue 2 (11th December 2020) - Wang, Jing; Lin, Yankun; Mohamed, Amel; Ji, Qingmin; Jia, Hongbing
Abstract : As a typical wettable, flexible, and biocompatible material, hydrogel has been a potential candidate for wearable electronics. Abstract : As a typical wettable, flexible, and biocompatible material, hydrogel has been a potential candidate for wearable electronics. However, it is still difficult for traditional hydrogels to integrate excellent mechanical properties and high-sensitivity. Herein, a novel conducting hydrogel was prepared via the in situ polymerization of polyaniline (PANI) combined with aramid nanofiber–polyvinyl alcohol (ANF–PVA) hydrogel as the template. On account of the interactions between ANF–PVA and conductive PANI, the ANF–PVA–PANI (APP) hydrogel has distinguished mechanical strength (2.4 MPa), tensile deformation (140%) and high sensitivity (gauge factor, GF = 39). The hydrogels are highly sensitive to strain changes and show stable resistance signals even after repeated sensing. When the hydrogels are assembled as wearable strain sensors, they provide precise response for monitoring joint motions of fingers, wrist pulse, cheek bulging, swallowing and speaking. This work provides a new inspiration for the design of wearable devices having both high mechanical strength and sensitivity.